RETRACTED: An Antifungal Mechanism of Protolichesterinic Acid from the Lichen Usnea albopunctata Lies in the Accumulation of Intracellular ROS and Mitochondria-Mediated Cell Death Due to Apoptosis in Candida tropicalis - Kumar, S. N.; Mohandas, C. (Frontiers in Pharmacology, 2017)
Candida species is a major opportunistic fungal pathogen, producing not only superficial mucosal infections but also cause human life-threatening systemic diseases (candidiasis). Protolichesterinic acid is a well-known lichen compound. Although the antibacterial activity of protolichesterinic acid have been reported earlier, the antifungal property and its mechanism of action are still largely unknown. The goal of this investigation is to explore the anticandidal activity and mechanism of action of protolichesterinic acid, especially against Candida tropicalis. The MIC value was established through microdilution techniques against four Candida species and out of four species tested, C. tropicalis showed a significant effect (MIC: 2 µg/ml). In the morphological interference assay, we observed the enhanced inhibition of hyphae when the cells were treated with protolichesterinic acid. Time-kill assay demonstrated that the maximum rate of killing was recorded between 2 to 6 h. C. tropicalis exposed to protolichesterinic acid exhibited an increased ROS production, which is one of the key factors of fungal death. The rise in ROS was due to the dysfunction of mitochondria caused by protolichesterinic acid. We confirmed that protolichesterinic acid-induced dysfunction of mitochondria in C. tropicalis. The damage of cell membrane due to protolichesterinic acid treatment was confirmed by the influx of propidium iodide and were further confirmed by the release of potassium ions. The treatment of protolichesterinic acid also triggered calcium ion signaling. Moreover, it commenced apoptosis which is clearly evidenced by Annexin V and propidium iodide staining. Interestingly protolichesterinic acid recorded excellent immunomodulatory property when tested against lymphocytes. Finally protolichesterinic acid showed low toxicity towards a normal human cell line Foreskin (FS) normal fibroblast. In in-vivo test, protolichesterinic acid greatly prolonged the survival of C. tropicalis infected Caenorhabditis elegans. This investigation proposes that the protolichesterinic acid induces apoptosis in C. tropicalis via the enhanced accumulation of intracellular ROS and mitochondrial damage, which leads fungal cell death via apoptosis. Our work revealed a new key aspect of mechanisms of action of protolichesterinic acid in Candida species. This article is the first study on the antifungal and mechanism of action of protolichesterinic acid in Candida species.